Perspectives in the study of the Old Testament and early Judiasm : a symposium in honour of Adams S. van der Woude on the occasion of his 70th birthday - Woude, A. S. van der.; Noort, Edward.; García Martínez, Florentino. (Vetus Testamentum, Supplements, 1998)
This volume contains the papers presented to a symposium organized by the Theological Faculty of the University of Groningen on the occasion of the seventieth birthday of Adam S. van der Woude, former Professor of Old Testament and Early Judaism and former head of the Qumran Institute at the same Faculty. The essays, eight in English and four in German, explore (through case studies) the developments over the last few years in the different areas of study of the Old Testament and of Early Judaism, observe the new perspectives opened in these areas and map the directions in which the research will be moving in the third millennium. The volume also includes a German version of the public lecture on the significance of the Dead Sea Scrolls for the Study of Old Testament and of Early Judaism delivered in Dutch by Van der Woude during the symposium.